2014
DOI: 10.1248/bpb.b13-00551
|View full text |Cite
|
Sign up to set email alerts
|

Distal Promoter Regions Are Responsible for Differential Regulation of Human Orosomucoid-1 and -2 Gene Expression and Acute Phase Responses

Abstract: Human orosomucoid (ORM) is a major acute-phase plasma protein, encoded by 2 highly homologous genes, ORM1 and ORM2. Human ORM induction is assumed to be regulated by each proximal promoter region, where putative glucocorticoid responsive elements and CCAAT/enhancer binding protein (C/EBP)β binding sites are located. However, the details of the differential regulation of these genes remain unknown. To explore this, we assessed the role of the distal promoter region of each ORM in HeLa cells. Luciferasereporter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…These data indicated that MSX ingestion mitigated liver inflammation induced by HFD consumption. Also, other inflammation markers, including serum amyloid A 1, 2, and 3 (Saa1, Saa2, and Saa3) 26) and orosomucoid 2 (Orm2) 27) which were not annotated with the immune response GO term, were down-regulated in the MSX group.…”
mentioning
confidence: 98%
“…These data indicated that MSX ingestion mitigated liver inflammation induced by HFD consumption. Also, other inflammation markers, including serum amyloid A 1, 2, and 3 (Saa1, Saa2, and Saa3) 26) and orosomucoid 2 (Orm2) 27) which were not annotated with the immune response GO term, were down-regulated in the MSX group.…”
mentioning
confidence: 98%
“…LCN2 is marker for liver damage and inflammation (Asimakopoulou et al, 2016;Moschen et al, 2017). Hepatic Lcn2 and Orm2 mRNAs are both upregulated in the liver in response to IL1B (Sai et al, 2014;Zhang et al, 2014). Saa1 and Saa2 mRNAs are acute phase response proteins and biomarkers of inflammation and their protein products become major components high density lipoprotein (HDL) regulated by IL1B (Leclerc et al, 2019;Lindhorst et al, 1997;Olteanu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It is also known to be a promoter of angiogenesis and histamine release . ORM‐1 is a key acute phase plasma protein increased during inflammation . In addition to angiogenesis promotion, vascular endothelial growth factor is also recognized as a proinflammatory mediator .…”
Section: Discussionmentioning
confidence: 99%
“…33 ORM-1 is a key acute phase plasma protein increased during inflammation. 34 In addition to angiogenesis promotion, vascular endothelial growth factor is also recognized as a proinflammatory mediator. 35 The genes of other mediators of inflammation were up regulated in the presence of CFNA: CSF1R is a receptor for colony-stimulating factor expressed by macrophages promoting the release of proinflammatory chemokines 36 ; Ly9 is a receptor promoting T-cell differentiation into a proinflammatory helper-T cell Th17 leading to increased IL-17 secretion 37 ; DNA damage-inducible transcript 3 positively regulates the transcription of tribbles homolog 3 and the proinflammatory cytokines IL-1 and IL-6; and IL-8 has been implicated in some allergic reactions.…”
Section: Discussionmentioning
confidence: 99%